Schwannoma of the Posterior Tibial Nerve Presenting as Tarsal Tunnel Syndrome: A Case Report with Emphasis on the Role of Microscope during Surgery - Raja Bhaskara Rajasekaran; Rajasekaran Shanmuganathan (Case Reports in Orthopedics)
Schwannoma is a benign, noninvasive tumour of the peripheral nerve sheath with rare occurrence in the extremities. We present a case of a schwannoma in the posterior tibial nerve which presented with symptoms suggestive of tarsal tunnel syndrome. The patient was managed with surgical excision of the tumour under microscope, and the diagnosis was confirmed by histopathology. Such a presentation is rare, and our case report adds light regarding the management of such cases.